A phase II pilot trial investigating the efficacy and activity of single agent granulocyte macrophage colony-stimulating factor as maintenance approach in castration - resistant prostate cancer patients responding to chemotherapy - Nabhan, Chadi; Meyer, Andrew; Tolzien, Kathy; Bitran, Jacob D; Lestingi, Timothy M (Avicenna Journal of Medicine, 2011)
Purpose: To investigate the toxicity and efficacy of GM-CSF in castration-resistant prostate cancer (CRPC) patients who maximized their response to systemic chemotherapy. Materials and Methods: CRPC patients who maximized their response to either docetaxel or mitoxantrone chemotherapy were eligible if they demonstrated adequate performance status, liver, kidney, and bone marrow function. Maximum response to chemotherapy was defined as either receiving at least 8 cycles of chemotherapy without radiographic or biochemical progression, receiving less than 8 cycles as long as the prostate-specific antigen (PSA) changes by less than 10%, or being off chemotherapy for less than 12 weeks without disease progression. Patients received GM-CSF at 250 mcg/m 2 subcutaneously for 14 days followed by 14 days of rest. GM-CSF was continued until disease progression. Results: Fifteen patients were enrolled of which all were evaluable for toxicity and 13 were evaluable for efficacy. Median age was 78 (range 66-96) and 93% of patients had a Gleason score ≥ 7. Biochemically, 2 patients (15.3%) attained partial response (PR) and 4 (30.7%) had stable disease (SD). Median time to PSA progression was 6 months (range 4-12). Radiographically, 9 patients (69.2%) had SD that lasted a median of 6 months (range 2-10). With a median follow-up of 24 months from starting GM-CSF (range 2-38), 2 patients (13.3%) remain alive and well. Median OS from start of any chemotherapy was 21 months (range 10-44). GM-CSF was well-tolerated with minimal expected manageable toxicities.Conclusions: GM-CSF is active post-chemotherapy in CRPC patients. Further studies with GM-CSF in this setting are warranted.
Keywords: Biologic therapy; castration-resistant; GM-CSF; hormone refractory; prostate cancer